2020
DOI: 10.1016/j.acuroe.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle among urology trainees and young urologist in the context of burn-out syndrome

Abstract: Introduction: Burnout syndrome has increased dramatically in urology within recent years. A healthy lifestyle has been described as a protective factor. However, data on lifestyle is lacking among residents and urologists and remains to be elucidated. We aim to assess lifestyle among urology residents and young urologists across Europe. Materials and methods: Members of the European Society of Residents in Urology(ESRU) designed a 34-item online survey via surveymonkey.com. The survey was designed in accordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Sedangkan menurut menurut Hasibuan (2014), beban kerja merupakan kemampuan tubuh dalam menerima pekerjaan. Kapasitas pekerjaan harus disesuaikan dengan jumlah karyawan yang ada (Atroszko, 2020;Chen, 2018;Cross, 2018;Jones, 2018;Kacem, 2020;Mohebbi, 2019;Pedersen, 2018;Poelmann, 2021;Rodríguez-Socarrás, 2020;Vang, 2020;Verougstraete, 2020;Yong, 2020).…”
Section: Pendahuluanunclassified
“…Sedangkan menurut menurut Hasibuan (2014), beban kerja merupakan kemampuan tubuh dalam menerima pekerjaan. Kapasitas pekerjaan harus disesuaikan dengan jumlah karyawan yang ada (Atroszko, 2020;Chen, 2018;Cross, 2018;Jones, 2018;Kacem, 2020;Mohebbi, 2019;Pedersen, 2018;Poelmann, 2021;Rodríguez-Socarrás, 2020;Vang, 2020;Verougstraete, 2020;Yong, 2020).…”
Section: Pendahuluanunclassified
“…Resources such as resilience training, support programs, structured mentorship programs, and access to mental health services have been associated with a lower rate of burnout [28][29][30]. Promoting wellness in general is a low-cost change that institutions can implement to positively impact the lives of urologists [30].…”
Section: Physician Burnoutmentioning
confidence: 99%
“…It was shown that factors associated with a healthy lifestyle prevent the development of emotional burnout [4,8,[13][14][15]. On the contrary, factors associated with an unhealthy lifestyle (alcohol and coffee consumption, insomnia, lack of vacation) cause burnout [16][17][18].…”
Section: Introductionmentioning
confidence: 99%